2020
DOI: 10.1186/s12966-020-01015-5
|View full text |Cite
|
Sign up to set email alerts
|

Social ecological factors associated with physical activity and screen time amongst mothers from disadvantaged neighbourhoods over three years

Abstract: Background: Mothers from socioeconomically disadvantaged neighbourhoods are at elevated risk of physical inactivity and high levels of screen time. Yet, little is known regarding the social ecological factors that are longitudinally associated with physical activity and screen time in this target group, and whether the age of their children impacts these relationships. This study aimed to longitudinally examine the social ecological factors associated with physical activity and screen time amongst mothers livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
0
13
0
1
Order By: Relevance
“…Our observed sex X support interaction identifies reporting a lack of social support has a stronger association with physical activity behavior for females than males. Several papers have similarly identified the importance of social support for women to engage in physical activity, where support is often related to caring responsibilities, social resources, and comfort accessing exercise facilities ( Cleland et al, 2012 ; Van Dyck et al, 2014 , Scarapicchia et al, 2017 , Morris et al, 2020 , Vrazel et al, 2008 , Wilson et al, 2022 ). Reduced gendered responsibilities (e.g., childcare, household tasks) are associated with greater odds of meeting physical activity guidelines for rural women ( Eyler, 2003 ), and tailored interventions to address gender-specific barriers are effective at increasing physical activity for women ( Segar et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our observed sex X support interaction identifies reporting a lack of social support has a stronger association with physical activity behavior for females than males. Several papers have similarly identified the importance of social support for women to engage in physical activity, where support is often related to caring responsibilities, social resources, and comfort accessing exercise facilities ( Cleland et al, 2012 ; Van Dyck et al, 2014 , Scarapicchia et al, 2017 , Morris et al, 2020 , Vrazel et al, 2008 , Wilson et al, 2022 ). Reduced gendered responsibilities (e.g., childcare, household tasks) are associated with greater odds of meeting physical activity guidelines for rural women ( Eyler, 2003 ), and tailored interventions to address gender-specific barriers are effective at increasing physical activity for women ( Segar et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Children’s screen time was found to be the result of an interaction between child and parent factors and was highly influenced by parental attitudes in another study [ 39 ]. A study focused on mothers from disadvantaged neighborhoods found that neighborhood cohesion was associated with screen time amongst mothers with both younger and older children [ 40 ]. A study among Chinese young children reported that, in rural areas, screen time was positively associated with traffic and limited places for and methods of outdoor play, and it was negatively associated with the importance of academics and the need for company [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Outro ponto que cabe ser destacado Ă© que mulheres que sĂŁo mĂŁes, que tem desvantagens socioeconĂŽmicas e residem em bairros mais populares, apresentam risco mais elevado de inatividade fĂ­sica e altos nĂ­veis de tempo de tela (Morris, Arundell, Cleland, & Teychenne, 2020). JĂĄ com relação aos homens a maior prevalĂȘncia de AFTL pode ser justificada pela cultura quanto aos motivos que levam os indivĂ­duos do sexo masculino, desde a infĂąncia, a serem incentivados a participar de atividades fĂ­sicas, principalmente as atividades coletivas, esportes e outras atividades mais vigorosas com maior gasto de energia (Dumith et al, 2016).…”
Section: Discussionunclassified